In-Band Scattering Control of Ultra-Wideband Tightly Coupled Dipole Arrays Based on Polarization-Selective Metamaterial Absorber - Zhang, Zhechen; Huang, Ming; Chen, Yikai; Qu, Shi-Wei; Hu, Jun; Yang, Shiwen (IEEE transactions on antennas and propagation, 2020)
With the polarization-selective metamaterial absorber (PSMA), a unique approach for reducing the in-band radar cross section (RCS) while preserving the radiation performance of a tightly coupled dipole array (TCDA) is proposed. The proposed PSMA structure is comprised of resistive films, dielectric layers, and polarization gates. In detail, the resistive films are loaded on the surface of a TCDA, and the polarization gates are utilized to broaden the absorption bandwidth of PSMA as well as to improve the polarization purity of the array. Moreover, the process of the co-design of the phased array with PSMA is presented. The designed infinite array is able to achieve a 3:1 bandwidth from 6 to 18 GHz with the active VSWR < 2.7 for the scan up to 60° in E-/H-plane. To verify the proposed approach, a 10 × 10 single-polarized prototype array is fabricated and measured. Measured results are in good agreement with simulated ones, thus demonstrating that the PSMA structure is able to reduce the scattering significantly throughout the operating band of the array under normal and oblique incidence.